Transcatheter aortic valve implantation for patients at high risk of surgical aortic valve replacement: initial experience. (22nd September 2015) - Baumbach, A; Kesavan, S; Hutter, J; Turner, M
Abstract : Transcatheter aortic valve implantation (TAVI) is rapidly becoming an accepted technology in high-risk patients with aortic stenosis not considered to be surgical candidates. We started the TAVI programme selecting patients over 80 years of age who were considered high-risk candidates for surgical aortic valve replacement (AVR), based on clinical assessment and risk scores. We excluded patients who were not suitable for surgery. Methods: 20 patients underwent TAVI for symptomatic aortic stenosis, using the self-expanding Corevalve device. The mean age was 84 years, the mean logistic EuroScore was 13.9%, 50% of the patients were women and 19 were in NYHA class III or IV. The aortic valve area was 0.5 cm 2, the peak gradient assessed by echocardiography was 93 mm Hg. 16 of 20 patients had an ejection fraction greater than 50%. Four patients had undergone previous coronary bypass surgery. Before TAVI, six patients underwent percutaneous coronary intervention for symptomatic coronary disease. 19 procedures were done via the femoral artery and one through the subclavian artery. Results: Procedural success was 100%. All patients had a major haemodynamic improvement. One femoral artery had to be closed surgically. One patient had a stroke. 19 of 20 patients reported a major clinical improvement. One patient with moderate aortic regurgitation and diastolic dysfunction will require repeat intervention. The median length of stay was 9 days. At 30 days there was no death or myocardial infarction and no structural valve dysfunction or migration. Four patients required a new pacemaker system. Conclusion: This is the first report of a series of octogenarians who were surgical candidates, but received TAVI instead of surgical AVR with good results and low complication rates.